PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VII SMP N 1 SINABOI SATU ATAP TAHUN PELAJARAN 2015/2016 - Fauziah, Yuslim; ', Ratnawati; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study is a class action that aims to improve the learning outcomes of students of class VII SMPN 1 Sinaboi Satu Atap 2015/2016 school year by implementing cooperative learning model type STAD. This research was conducted in two cycles of planning, implementation, observation and reflection. The parameters in this study is the thoroughness of learning outcomes derived from the value of post tets and the daily test, student activities and teacher's activities are collected using observation sheet. The results showedabsorption in the first cycle was 69.24% (or less) and the second cycle increased to 87.2% (good). Mastery learning students in the first cycle that 74.96% (enough) and the second cycle increased to 81.04% (excellent).Group awards in the first cycle, one predicated super group and4 great predicated group. In the second cycle, the 2 groups and 3 groups predicated predicated super great. Learning activities of students during a discussion with the implementation of cooperative learning model STAD first cycle is 81% (good) increased to 93.87% (excellent) on the second cycle. Activities teachers in the learning process in the first cycle is 75%, (enough) and the second cycle was 95% (excellent). It can be concluded that the implementation of cooperative learning model STAD can improve learning outcomes IPA class VII SMPN 1 Sinaboi Atap school year 2015/2016.Keywords : STAD cooperative mode, IPA Learning Outcomes